Evaluation of repeated X-ray procedures and cost implications of the radiology department of general hospital Katsina-Nigeria - Sani, Usman; Idris, Mustapha Muhammed (Universitas Sebelas Maret, 2000)
Repeated X-ray procedures contribute immensely to the unnecessary radiation exposure of patient and staff, additional health care costs, increased in time and over workload of the x-ray modalities. It is clearly known that low radiation doses are associated with the stochastic effects which includes cancer. The main aim of this study is to evaluate the repeated x-ray procedures and cost implication of the radiology department of General Hospital Katsina, Nigeria. The retrospective study of 4985 patients was carried for a period of 12-month, from January, 2023 to December, 2023. The results revealed 1216 rejected films out of 4985 with positioning error accounting for 21%, image cutoff 19.5% and under exposure 17.7%. The overall reject rate of 24.34% was recorded. The total sum of #2, 420,100 ( 1,512.66) was spent on the repeated x-ray procedures. The reject rate of 24.39% was above the recommended reject rate of 10% as recommended by AAPM. This study recommends the need for effective quality assurance and quality control protocols and enhanced staff training in image positioning and optimization of radio-diagnostic image quality.